Identification of long non-coding RNAs in response to nanopolystyrene in Caenorhabditis elegans after long-term and low-dose exposure. (December 2019) - Qu, Man; Zhao, Yunli; Zhao, Yingyue; Rui, Qi; Kong, Yan; Wang, Dayong
Abstract: The potential adverse effects of nanoplastics, such as nanopolystyrene, have received the great attention recently. However, the molecular response of organisms to nanoplastics is still largely unknown. In this study, we employed Caenorhabditis elegans as an animal model to investigate the long non-coding RNAs (lncRNAs) in response to long-term exposure to low-dose nanopolystyrene (100 nm). Based on Hiseq 2000 sequencing and qRT-PCR confirmation, we identified 36 lncRNAs (21 down-regulated lncRNAs and 15 up-regulated lncRNAs) in response to nanopolystyrene (1 μg/L). Using intestinal reactive oxygen species (ROS) production and locomotion behavior as endpoints, we found that RNAi knockdown of linc-2, linc-9, or linc-61 induced a susceptibility to nanopolystyrene toxicity, and RNAi knockdown of linc-18 or linc-50 induced a resistance to nanopolystyrene toxicity. Meanwhile, nanopolystyrene (1 μg/L) increased expressions of linc-2, linc-9, linc-18, and linc-61 and decreased linc-50 expression, suggesting that these 5 lncRNAs mediated two different responses to nanopolystyrene exposure. Bioinformatical analysis implied that these 5 lncRNAs were associated with multiple biological processes and signaling pathways. Our results demonstrated the crucial roles of lncRNAs in response to long-term exposure to low-dose nanopolystyrene in organisms. Graphical abstract: Long-term and low-dose exposure to nanopolystyrene induced the response of limited number of lncRNAs and two different lncRNA responses in nematodes. Image 1 Highlights: LncRNAs responses to nanopolystyrene were examined in Caenorhabditis elegans. We identified 37 lncRNAs in response to nanopolystyrene (1 μg/L). We confirmed functions of 5 known lncRNAs in regulating nanopolystyrene toxicity. Intestinal ROS production and locomotion behavior were used as endpoints. Abstract : Long-term exposure to low-dose nanopolystyrene only induced the response of limited number of lncRNAs in nematodes.